Republic of Croatia : Staff Report for 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Until recently, Croatia's economic performance was the envy of many countries in transition: a successful stabilization effort in late 1993 was followed by virtual price stability and real GDP growth of 6 percent a year during 1994-97. Monetary tightening, the weak economy, and a drying-up of repatriated foreign savings exposed the underlying insolvency of a group of rapidly growing banks. Executive Directors emphasized that the task of restoring fiscal balance could not be accomplished without redressing the finances of the pension and health care systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet